1982
DOI: 10.1007/bf00392782
|View full text |Cite
|
Sign up to set email alerts
|

Purification of glycollate oxidase from greening cucumber cotyledons

Abstract: Glycollate oxidase (glycollate: oxygen oxidoreductase, EC 1.1.3.1) was purified to apparent homogeneity from crude extracts of greening cucumber cotyledons (Cucumis sat vus). Molecular sieving and chromatofocusing resulted in 700-fold purification and specific activity of 1 μkat mg(-1) protein. The enzyme exhibited a Mr of 180,000, or 700,000, respectively, and is a tetramer or 16-mer made of identical subunits of Mr 43,000. Monospecific antibodies were raised against the homogeneous protein.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
16
0

Year Published

1990
1990
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 16 publications
2
16
0
Order By: Relevance
“…Poly(A+) RNA was prepared from the green leaves and used as template for preparation of cDNA (9,10). The presence of translatable glycolate oxidase mRNA was evidenced by translation in vitro and subsequent immunoprecipitation with anti-glycolate oxidase antiserum (4). cDNA was obtained using the cDNA synthesis kit and the procedure of Pharmacia (Uppsala, Sweden) for purification by phenol extraction and chromatography on Sephacryl S-200.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Poly(A+) RNA was prepared from the green leaves and used as template for preparation of cDNA (9,10). The presence of translatable glycolate oxidase mRNA was evidenced by translation in vitro and subsequent immunoprecipitation with anti-glycolate oxidase antiserum (4). cDNA was obtained using the cDNA synthesis kit and the procedure of Pharmacia (Uppsala, Sweden) for purification by phenol extraction and chromatography on Sephacryl S-200.…”
Section: Methodsmentioning
confidence: 99%
“…The filters were washed twice for 10 min each time in 2x SSC and 0.1% SDS. Positive clones were examined both by rescreening with insert of pE56 and by screening with antibodies against lentil glycolate oxidase (4).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This oxidase also oxidized glycolic acid to glyoxylic acid. The oxidative reaction of glycolic acid has been studied in detail using some glycolate oxidases (glycolate: oxygen oxidoreductase, Ee 1.1.3.1) from green plants such as spinach,4) pea, 5) pumpkin,6) tabacco,7) and cucumber, 8) and lactate oxidase 9 ) (L-Iactate: oxygen 2-oxidoreductase (decarboxylating), Ee 1.13.12.4) from Mycobacterium smegma tis, but not with fungal enzymes. This paper describes some characterizations of the oxidative reaction of ethylene glycol and glycolic acid by glycerol oxidase and provides an evaluation of glycerol oxidase for the production of glyoxal and glyoxylic acid.…”
mentioning
confidence: 99%
“…Its absorbance at 280 nm was rather low and in fair agreement with Trp content, and its molecular mass (37 760 Da), as derived from Table II, was consistent with that obtained by SDS-polyacrylamide gel electrophoresis. Since a value of 169 kDa was obtained under nondenaturing conditions (not shown), it was concluded that chicken liver L-2-HAOX A is composed of 4 apparently identical subunits as all the enzymes of the A-type so far isolated from mammals [3,7] and plants [13,20].…”
Section: Some Molecular Propertiesmentioning
confidence: 96%